The Gene ANTHER DEHISCENCE REPRESSOR (ADR) Controls Male Fertility by Suppressing the ROS Accumulation and Anther Cell Wall Thickening in Arabidopsis - Dai, Shu-Yu (Sci Rep, 2019)
Male sterility in plants is caused by various stimuli such as hormone changes, stress, cytoplasmic alterations and nuclear gene mutations. The gene ANTHER DEHISCENCE REPRESSOR (ADR), which is involved in regulating male sterility in Arabidopsis, was functionally analyzed in this study. In ADR::GUS flowers, strong GUS activity was detected in the anthers of young flower buds but was low in mature flowers. ADR + GFP fusion proteins, which can be modified by N-myristoylation, were targeted to peroxisomes. Ectopic expression of ADR in transgenic Arabidopsis plants resulted in male sterility due to anther indehiscence. The defect in anther dehiscence in 35S::ADR flowers is due to the reduction of ROS accumulation, alteration of the secondary thickening in the anther endothecium and suppression of the expression of NST1 and NST2, which are required for anther dehiscence through regulation of secondary wall thickening in anther endothecial cells. This defect could be rescued by external application of hydrogen peroxide (H(2)O(2)). These results demonstrated that ADR must be N-myristoylated and targeted to the peroxisome during the early stages of flower development to negatively regulate anther dehiscence by suppressing ROS accumulation and NST1/NST2 expression.